Multidisciplinary analysis of the Hapi region located on Comet 67P/Churyumov–Gerasimenko. Issue 2 (7th March 2019) - Pajola, M; Lee, J-C; Oklay, N; Hviid, S F; Penasa, L; Mottola, S; Shi, X; Fornasier, S; Davidsson, B; Giacomini, L; Lucchetti, A; Massironi, M; et al.
ABSTRACT: By using the Rosetta /OSIRIS-NAC data set taken in 2014 August, we focus on the neck region, called Hapi, located on 67P Churyumov–Gerasimenko's Northern hemisphere. The gravitational potential and slopes of Hapi, coupled with the geological unit identification and the boulder size–frequency distributions, support the interpretation that both taluses and gravitational accumulation deposits observable on Hapi are the result of multiple cliff collapses that occurred at different times. By contrast, the fine-particle deposits observable in the central part of the study area are made of aggregates coming from the Southern hemisphere and deposited during each perihelion passage. Both the consolidated terrains on the western part of Hapi, as well as the centrally aligned ridge made of boulder-like features, suggest that Hapi is in structural continuity with the onion-like structure of the main lobe of 67P. Despite the dusty blanket observable on Hapi, its terrains are characterized by water-ice-rich components that, once repeatedly and rapidly illuminated, sublimate, hence resulting in the strong jet activity observed in 2014 August.